Internal Rhythm in Abd al-Wahhāb al-Bayāti Poetry: The Poetical Divan of al-Mowt Fi-l-Hayāt - Raja Abū Ali; Manizhe Zare (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2012)
As a word having a Greek root, Rhythm (Iqa') means "to flow, to be in stream". In poetry, however, it means the regular sequences of a series of phonological as well as non-phonological elements, making poetry seem beautiful. As one of the most important parts of the poem, rhythm is divided into internal and external one. Becauuse of thefreedom of new poetry from rhyme and rhyming rhythm, the importance of external rhythm having had these two elements, is decreasing while the internal rhythm has played an important role in new poetry. Firstly, this paper defines the rhythm of music and its application into critical works. Secondly, the paper examines closely the internal rhythm and it's componants in Abd al-Wahhab al-Bayāti’s poetry – Iraqi's contemporary poet – with regard to al-Mowt fi-l-Hayāt. Intrenal rhythm has two kinds: phonological and meaning-based rhythm, or so-called the rhytm of thought. Phonological rhythm studies such features as pun and different types of repetition and meaning-based rhythm examines such features as antithesis, symbol and myth, parallelism and apostrophe (Iltifāt). The methodology is analytic-descriptive through the means of the library studies.